1999
DOI: 10.2527/1999.773637x
|View full text |Cite
|
Sign up to set email alerts
|

Beef customer satisfaction: cooking method and degree of doneness effects on the top loin steak.

Abstract: The objective of this research was to evaluate the consumer-controlled factors of cooking method and degree of doneness on Top Choice, Low Choice, High Select, and Low Select top loin steaks. The in-home product test was conducted in Chicago, Houston, Philadelphia, and San Francisco. Consumers (n = 2,212) evaluated each top loin steak for overall like (OLIKE), tenderness (TEND), juiciness (JUIC), flavor desirability (DFLAV), and flavor intensity (IFLAV) using 23-point hedonic scales. Respondents in San Francis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 10 publications
6
58
1
Order By: Relevance
“…Guelker et al (2013) and Voges et al (2007) both reported no significant differences across grades and sensory panel ratings for top loin foodservice steaks. This differs from data reported by Lorenzen et al (1999) who found differences between Top Choice and Select for overall liking. In regard to top sirloin foodservice steaks, there were no significant differences in the sensory ratings between grades (Table 11).…”
Section: Foodservice Consumer Sensory Evaluationscontrasting
confidence: 57%
“…Guelker et al (2013) and Voges et al (2007) both reported no significant differences across grades and sensory panel ratings for top loin foodservice steaks. This differs from data reported by Lorenzen et al (1999) who found differences between Top Choice and Select for overall liking. In regard to top sirloin foodservice steaks, there were no significant differences in the sensory ratings between grades (Table 11).…”
Section: Foodservice Consumer Sensory Evaluationscontrasting
confidence: 57%
“…This is supported by the work of Lorenzen et al (1999) and Neely et al (1999) who both found that consumers in different geographical areas scored beef sensory quality differently. However, it is also possible that the analysis was not sensitive enough to pick up such a small effect in the smaller number of consumers tested in Ireland.…”
supporting
confidence: 49%
“…More specifically, panel flavor scores improved as the marbling of beef increased (Lorenzen et al, 1999(Lorenzen et al, , 2003. In contrast, Voges et al (2007) reported sensory panel ratings for tenderness, juiciness, flavor hking, and overall liking did not differ across quality grades from Prime to Select for top loin steaks.…”
Section: Introductionmentioning
confidence: 64%
“…'Fat percentage of quality treatment listed in parentheses. ies have shown increased marbling level was associated with greater tenderness, juiciness, flavor, and overall palatability scores (Smith et al, 1985;Lorenzen et al, 1999Lorenzen et al, , 2003Carmyn et al, 2011). In the current study, a decrease in juiciness was observed as fat content decreased from Wagyu to Standard.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation